Early Slavic short and long o and e - Pronk, Tijmen (Slavia Centralis, 2020)
The articlediscusses the development of the Proto-Slavic vowels *o and *e with a neoacute accent. These vowels are reflected as short vowels, diphthongs or long vowels in the modern Slavic languages. Their outcome is conditioned by the origin of the neoacute: if it arose through retraction of the accent from a word-final jer, the newly accented *o or *e became long and was subsequently diphthongized in a number of Slavic dialects. If the neoacute accent arose in a different way, the quantity of the newly accented *o or *e depends on the dialect.